TRANSITIVITY SYSTEM ON THE LYRICS OF GERMAN CHILDREN’S SONG: FUNCTIONAL LINGUISTICS STUDIES - Ayu Putri, Nurul Mawaddah; Maknun, Tadjuddin; Lukman, Lukman (Universitas Hasanuddin, 2020)
The research aimed to analyze the type of transitivity process, genre structure, and to show the dominant kind of process on the lyrics of German children song. This research is descriptive qualitative research and supported by quantitative data. The data sources of the study are the lyrics of the German children song. The population of this research is all of the clauses on the lyrics of German children song. The research sample is clauses in the lyrics of German children song. The lyrics contain elements of transitivity sorted out purposively. The analysis used in this research is Halliday transitivity system analysis. The research finding indicated that (1) The type of process which was found in the analysis of the lyrics of German children’s song consists of six processes that are the relational process, the material process, the mental process, the verbal process, the existential process, and the behavioural process. (2) The kind of genre was found on the lyrics of German children’s song was two kinds of a genre that is narrative genre and stories genre. The result of the analysis of genre structure on the lyrics of German children’s song concluded that were not all of the elements of the genre structure were found on the lyrics. (3) The dominated process is the relational process that was represented by human and environmental social life.